The mobile connection the cell phone's impact on society - Ling, Richard Seyler (San Francisco, CA : Morgan Kaufmann, 2004)
"Based on research conducted in dozens of countries, this book examines the once-unexpected interaction between humans and cell phones, and between humans, period. The discussion and projections about the future of the telephone should give designers everywhere a more informed practice and process, and provide researchers with new ideas to last years."--Book jacket.
1. Introduction -- The history of mobile telephony -- The growth of the mobile market -- Outline of the book -- 2. Making sense of mobile telephone adoption -- The interaction between technology and society -- Technical/social determinism and affordances -- The domestication of Information and communication technologies (ICTs) -- Methods and data sources -- 3. Safety and security -- Introduction -- The mobile telephone as a contribution to security -- Use in situations where there is a chronic or an acute need for contact -- Abstraction of security vis-αa-vis mobile telephony -- The mobile telephone in extraordinary situations -- Diminution of safety -- Driving and mobile telephone use -- Personal privacy -- Conclusion -- 4. The coordination of everyday life -- Introduction -- Social coordination -- Mechanical timekeeping and social coordination -- The development of mechanical timekeeping -- The standardization of time -- The etiquette of time and timekeeping -- Mobile communication and microcoordination -- Midcourse adjustment -- Iterative coordination -- Softening of schedules -- Time-based vs. mobile-based coordination -- Advantages of mobile based coordination -- Limitations -- Competition or supplement -- Conclusion -- 5. The mobile telephone and teens -- Introduction -- Child/adolescent development and the adoption of telephony -- Adolescence and emancipation in contemporary society -- Elements in the adoption of mobile telephony by teens -- Functional uses of the mobile telephone among adolescents -- Symbolic meaning of the mobile telephone -- Social networking via the mobile telephone -- The monetary dimensions to teens' adoption of mobile telephony -- Conclusion : mobile telephony and the dance of emancipation -- 6. The intrusive nature of mobile telephony -- Introduction -- Mobile telephony in settings with heavy normative expectations -- Mobile telephony in interpersonal situations -- Initiation of the call and the production of social partitions -- Management of the local situation during the call -- Reemergence into the local setting -- Forced eavesdropping and being embarrassed for others -- Conclusion -- 7. Texting and the growth of asynchronous discourse -- Introduction -- The growth of texting -- Texting and the individual -- Texting and the group -- What is being said, who is saying it, and how do they say it -- Content of the messages -- Mechanics of SMS writing -- Written vs. spoken language -- Gendering of text messages -- The future of texting -- 8. Conclusion : the consequences of Osborne's prognosis -- Introduction -- Interaction between innovation and social institutions -- History of technical innovation and social adoption -- Sociology and the role of technical innovation -- Social capital vs. individualism -- Social capital -- The institutionalization of individualization -- The role of ICTs in the fostering of social capital/individualism -- The Internet -- The mobile telephone -- Ad hoc networks -- Virtual walled communities -- Appendix. Data sources used in the analysis of mobile telephony.
Includes bibliographical references (p. 223-237) and index.
Keywords: Cell phone systems -- Social aspects; Electronic books